Laser ignitability of insensitive propellants - Fang, Xiao; Ahmad, Sheikh R. (OAT, 2018)
Laser ignition tests were conducted on insensitive propellants formulated with an insensitive filler (1,1‑diamino-2,2-dinitroethylene, commercially known as FOX-7) and with either energetic or non-energetic binders: poly3-nitromethyl-3-methyloxetane (PolyNIMMO) and hydroxyl-terminated polybutadiene (HTPB), respectively. The tests were conducted in an unconfined environment using both visible (514 nm) and near infrared (808 nm) lasers. The non-energetic binder rendered the formulated ammunition more susceptible to initiation by the visible laser. The graph of ignition delay times versus laser power density followed the expected asymptotic trend. However, the shape of the ignition map was greatly affected by the beam area on the target. The results of the unconfined laser ignition tests were analysed to determine the feasibility of using lasers as cost-effective and safe igniters for future weapons and rocket motor systems.
Keywords: propellant; FOX-7; laser; ignition